(untitled) - Kandera, Branislav (Doprava a spoje, 2011)
Onboard Collision Avoidance System ACAS (Airborne Collision Avoidance System) aircraft is a system that uses signals SSR which operates independently of terrestrial radionavigations and surveillance systems, providing information on pilots operating in the vicinity of the aircraft while it is necessary that other aircraft were also equipped with an SSR transponder.